Different Effects of p52SHC1 and p52SHC3 on the Cell Cycle of Neurons and Neural Stem Cells. Issue 1 (28th September 2015) - Tang, Ning; Lyu, Dan; Liu, Tao; Chen, Fangjin; Jing, Shuqian; Hao, Tianyu; Liu, Shaojun
Abstract : SHC3 is exclusively expressed in postmitotic neurons, while SHC1 is found in neural stem cells and neural precursor cells but absent in mature neurons. In this study, we discovered that suppression of p52SHC1 expression by RNA interference resulted in proliferation defects in neural stem cells, along with significantly reduced protein levels of cyclin E and cyclin A. At the same time, p52SHC3 RNAi caused cell cycle re‐entry (9.54% in S phase and 5.70% in G2‐M phase) in primary neurons with significantly up‐regulated expression of cyclin D1, cyclin E, cyclin A, CDK2, and phosphorylated CDK2. When p52SHC3 was overexpressed, the cell cycle of neural stem cells was arrested with reduced protein levels of cyclin D1, cyclin E, and cyclin A, while overexpression of p52SHC1 did not result in significant changes in postmitotic neurons. Our results indicate that p52SHC3 plays an important role in maintaining the mitotic quiescence of neurons, while p52SHC1 regulates the proliferation of neural stem cells. J. Cell. Physiol. 230: 172–180, 2016. © 2015 Wiley Periodicals, Inc.